2014
DOI: 10.1109/tuffc.2014.2924
|View full text |Cite
|
Sign up to set email alerts
|

Electrode position optimization in magnetoelectric sensors based on magnetostrictive-piezoelectric bilayers on cantilever substrates

Abstract: Finite element method (FEM) simulations are performed to investigate the sensitivity to dc magnetic fields of magnetoelectric sensors on cantilever substrates with trenches or weights at different positions. For a simple layered cantilever, a 15% higher signal voltage across the piezoelectric layer is obtained for optimally positioned electrodes and an insulating magnetostrictive material. A further 25% increase in the signal voltage is achieved for a trenched cantilever design with a pick-up region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Due to the resonant bending, highest potentials are induced close to the clamped end of the cantilever and vanishing at the tip. The electric potential is averaged because of the electrode's conductivity and thus highest ME coefficients occur for small electrode lengths located close to the clamping with large piezoelectric layer thicknesses [9]. The corresponding short-circuit ME coefficient in Figure 3 (b) shows completely different behaviour with highest ME coefficients for largest electrode length and vanishing piezoelectric layer thickness.…”
Section: Finite Element Methods Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to the resonant bending, highest potentials are induced close to the clamped end of the cantilever and vanishing at the tip. The electric potential is averaged because of the electrode's conductivity and thus highest ME coefficients occur for small electrode lengths located close to the clamping with large piezoelectric layer thicknesses [9]. The corresponding short-circuit ME coefficient in Figure 3 (b) shows completely different behaviour with highest ME coefficients for largest electrode length and vanishing piezoelectric layer thickness.…”
Section: Finite Element Methods Resultsmentioning
confidence: 98%
“…It has been shown that the output signal can be enhanced by using magnetic flux concentrators [3]- [5], preventing air damping [6] and the use of optimized layer thicknesses and sequences [7], [8]. Furthermore, we have shown that the use of pick-up regions can further increase the electric potential [9]. However, beside the ME sensor's output signal the intrinsic noise level and lownoise amplifiers are of prime importance to measure small AC magnetic fields, for example in biomedical applications [10]- [12].…”
Section: Introductionmentioning
confidence: 87%
“…This suggests that electrodes should only be deposited at the positions with higher ME response. 15,16 Nevertheless, few studies have reported circuit optimization of the electrodes on a single laminate. Based on these facts, PZT/Ni cylindrical layered ME composites with quartering electroplated Ni arc layers, which also serve as the positive electrodes, were designed.…”
mentioning
confidence: 99%